The Urgency of Regulating Sexual Extortion in Online Gender-Based Violence from a Criminal Law Perspective - Mellisa Anggraini (Journal of Law, Politic and Humanities, 2024)
With the increasing types and forms of Online Gender-Based Sexual Crimes (OGBSC) in this modern era, especially through sexual extortion, it raises the question of whether sexual extortion in OGBSC should still be categorized as extortion. Given that sexual extortion is closely related to the crime of disseminating intimate content through the internet, it is necessary to analyze the legal basis used to criminalize perpetrators of sexual extortion who disseminate intimate content on cyberspace. This paper discusses the Legal Problems of Sexual Extortion with the Motive of Threats of Dissemination of Intimate Content in Indonesia and the Urgency of Regulating Sexual Extortion in Online Gender-Based Violence from a Criminal Law Perspective. The research method uses normative legal research. The results of the study show that cases of sexual extortion in Indonesia related to the dissemination of intimate content due to the perpetrator's threats being ignored, such as in Decision Number 182/Pid.B/2018/PN.Smn and Number 56/Pid.Sus/2019/PN.Mks., both criminalize the perpetrator's actions in disseminating intimate content belonging to the victim, because the victim did not fulfill the perpetrator's wishes in the form of an invitation to marry and money, but the Public Prosecutor or judge ignored the extortion committed by the perpetrator, but only punished the perpetrator with the article on the act of disseminating intimate content and the article on threats of violence or intimidation. So the government needs to improve the articles in the Crime of Sexual Violence Law regarding electronic-based sexual violence, by adding the main crime of sexual extortion.